Machiavelli's God - Viroli, Maurizio (Book collections on Project MUSE., 2010)
To many readers of The Prince, Machiavelli appears to be deeply un-Christian or even anti-Christian, a cynic who thinks rulers should use religion only to keep their subjects in check. But in Machiavelli's God, Maurizio Viroli, one of the world's leading authorities on Machiavelli, argues that Machiavelli, far from opposing Christianity, thought it was crucial to republican social and political renewal--but that first it needed to be renewed itself. And without understanding this, Viroli contends, it is impossible to comprehend Machiavelli's thought.